ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA BERDASARKAN GAYA BELAJAR - Fitriana, Eva; Lutfiyah (At- Ta'lim : Jurnal Pendidikan, 2023)
The purpose of this research is to analyze students' critical thinking skills based on learning styles. The type of research used is descriptive qualitative. The research subjects were class VIII students of SMP PGRI Jenggawah, Jember Regency. There are 3 test subjects with one participant from visual, auditory/auditory, kinesthetic. The information in the research was generated from learning style polls, student test sheets, and interviews. The procedures for examining information in this study are information reduction, information disclosure, and reaching determination. Polling data is filled in to determine student learning style tendencies, while test sheets are used to determine students' reasoning abilities. The results showed that the reasoning abilities that determine students in each learning style have different levels. Students with a visual learning style can basically think in a high classification with a score of 75, students with an auditory learning style can think fundamentally in a moderate classification with a score of 62.5, while students with a kinesthetic learning style can think basically. in very low classification with a score of 31.25. In accordance with the learning style, producing a visual learning style has a decisive reasoning ability that is better than listening/auditory and kinesthetic abilities